Types of Directive Speech Acts in “Fall” Movie 2022 - Marisa Anggraini; Afriana Afriana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research investigates the types of directive speech acts in the movie "Fall" which was released in 2022. The data in this research were taken from the utterances produced by the characters in the movie "Fall". This study uses a descriptive qualitative method from Creswell (2018), because the data are in the form of words and phrases. The theory from Yule (1996) was applied to identify the types of directive speech acts in the data sources. Then, this research applies the theory from Sudaryanto (2015) about the observation method and non- participation techniques used to collect data from the movie. The results showed that there were 21 directive speech act data in the movie "Fall". And the 10 data are divided into 5 types of directive speech acts. Those were 3 command data, 7 command data, 5 request data, 4 suggestion data, and 2 suggestion data. The type of request is the most used type of directive speech act in the movie "Fall" 2022.